Controllable construction of ZnO/TiO2 patterning nanostructures by superhydrophilic/superhydrophobic templates - Lai, Yuekun (2013)
Position- and orientation-controllable micropatterned ZnO/TiO2 nanostructures with different morphologies have been fabricated using a novel and versatile superhydrophilic/superhydrophobic template. Scanning electron microscopy, optical microscopy, electron probe microanalysis and X-ray diffraction were systematically used to confirm the successful fabrication of the patterns and to characterize the structure and morphology. The selective growth of ordered ZnO nanostructured patterns on the TiO2 nanotube surface employs a simple photocatalytic lithography technique with mild reaction conditions and in the absence of seeds and noble metal catalysts. The photoelectrical properties of the micropatterned ZnO/TiO2 nanocomposites with unique heterojunction structure and different density and orientation of the ZnO crystals were also investigated. It is expected that this novel micropatterned technique based on the superhydrophilic/superhydrophobic template will become a powerful tool for fabricating various types of micropatterned nanomaterials and devices.